Global Health Governance: The Political Dimensions of the Pandemic Response - Budiana, Muhammad (Yayasan Pendidikan Belajar Berdikari, 2024)
This study explores the political dimensions of global health governance with a focus on pandemic response, covering aspects of the influence of political interests, unequal access to health resources, and the effectiveness of international collaboration. The results show that national political interests are often a barrier to effective global collaboration. Many countries prioritize their own citizens through vaccine protectionism policies, and large countries use vaccines as a diplomatic tool to expand their influence. On the other hand, unequal access to vaccines and medical equipment exposes a clear gap between developed and developing countries. In conclusion, this pandemic highlights the urgent need for global health governance reforms, including a strengthened role for WHO, increased equity in the distribution of health resources, and stronger cooperation among countries to improve preparedness for future health crises.